(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Iru, a traditional fermented condiment widely consumed in West Africa, is produced from the seeds of Parkia biglobosa (African locust bean) and Prosopis Africana (Mesquite/Okpehe). The quality and safety of Iru can be significantly affected by fungal contaminants during processing and storage. This study aims to compare the fungal contaminants present in Iru produced from Parkia biglobosa and Prosopis Africana, examining their impact on the nutritional and microbial quality of the final product. Standard mycological techniques were used to isolate and identify fungal species using Potato dextrose agar (PDA). The microbial load, proximate composition, and physicochemical properties of the samples were analysed to assess the quality and safety of the fermented products. Results showed that Parkia biglobosa Iru exhibited a higher diversity of fungal species compared to Prosopis Africana Iru. Aspergillus niger and Sacharomyces cerevisiae were the most prevalent with (23.81%) each while Penicillium chrysogenum has the least prevalence (1.0%). This diversity poses a greater risk of mycotoxin contamination in Iru from Parkia biglobosa. Both Prosopis Africana and Parkia bioglobosa offers significant nutritional benefits but Parkia generally has higher moisture content, protein and fat content while Prosopis contains higher fibre, ash content and carbohydrates which aids metabolic process overall nutritional value and energy source respectively.